Application of the Vendor Managed Inventory (VMI) Model Based on Total Distribution Cost Optimization - Giovano Alberto; Alexander Jimmy (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study develops an optimization-based Vendor-Managed Inventory (VMI) model to improve coordination between inventory and transportation decisions in an upstream automotive distribution network in West Java. The problem is formulated as a multi-period Inventory Routing Problem (IRP) and solved using AMPL with CPLEX. The model minimizes total logistics cost, including transportation and inventory holding costs. A benchmark comparison with the company’s existing decentralized replenishment policy is conducted. Results show that the proposed VMI model reduces total monthly logistics cost by 10.66%, from IDR 2.74 billion to IDR 2.44 billion. In addition, service performance improves significantly, with demand fulfilment increasing from 91.3% to 99.2% and stock-out occurrences eliminated. The findings highlight the importance of integrated decision-making in freight distribution systems and provide practical insights for transport capacity planning and inventory positioning.